Analysis of the Determinants of the Technology Acceptance Model (TAM) on the Use of Hospital Management Information Systems Among Young Dentists in the Outpatient Unit of Prof. Dr. Moestopo Dental and Oral Teaching Hospital - Ramadhani, Mahila Fariha; Sunadi, Apri; Aziz, Abdul (International Journal of Business, Law, and Education, 2025)
Background: The Hospital Management Information System (HMIS) is a crucial component in enhancing the quality of healthcare services. The successful implementation of HMIS largely depends on the acceptance and actual use by healthcare professionals. Objective: This study aims to analyze the determinants influencing the acceptance and utilization of HMIS at the Prof. Dr. Moestopo Dental and Oral Teaching Hospital, using the Technology Acceptance Model (TAM) framework. Methods: This study employed a quantitative approach with a cross-sectional design. The study population consisted of 182 individuals, from which 122 young dentists were selected using purposive sampling. Data were collected using a validated and reliable questionnaire. The data analysis involved bivariate tests (Chi-Square), Spearman correlation, and multivariate logistic regression analysis. Results: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Attitude Toward Use (ATU) significantly influenced the actual use of HMIS, while Behavioral Intention (BI) showed no significant effect. Conclusion: The successful use of HMIS is determined by perceived usefulness, ease of use, and user attitudes toward the system. Recommendations: Strengthening these determinants through continuous dissemination of HMIS benefits, sustained training programs, and enhanced motivation among healthcare professionals is essential to improve system utilization.